2015
DOI: 10.1039/c5ra07865b
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight and solution processible thin sheets of poly(o-toluidine)-carbon fiber-novolac composite for EMI shielding

Abstract: An attempt has been made to generate lightweight and processible thin sheets of poly (o-toluidine)-carbon fiber (PoTCF) composite for electromagnetic interference shielding. PoTCF composite synthesized by oxidative emulsion polymerization was physically blended with different weight ratios of novolac resin to prepare a new class of composite material, which was further processed to form thin sheets (thickness of $0.85 mm) by a compression moulding technique. In situ incorporation of carbon fiber into the polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 37 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…The polypyrrole/nylon-6 fabric composite prepared by multiple depositions of polypyrrole layers onto nylon-6 could effectively be used in EMI shielding with an attenuation of 40 dB in the 50 MHz-13.5 GHz frequency range [10]. The results of a very recent study including the preparation of poly(o-toluidine)/carbon fiber/novalac thin sheets showed that the material could have potential uses in durable enclosures for electronic equipment with an EMSE performance of 24 dB at 8-12 GHz [11]. Studies on the EMI shielding performances of polypyrrole/nylon-lycra [12], polythiophene/PET [13], polyaniline/carbon fiber [14] polyaniline/cotton [15,16], and polyethylenedioxythiophene/PET [17] were also examined under different frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The polypyrrole/nylon-6 fabric composite prepared by multiple depositions of polypyrrole layers onto nylon-6 could effectively be used in EMI shielding with an attenuation of 40 dB in the 50 MHz-13.5 GHz frequency range [10]. The results of a very recent study including the preparation of poly(o-toluidine)/carbon fiber/novalac thin sheets showed that the material could have potential uses in durable enclosures for electronic equipment with an EMSE performance of 24 dB at 8-12 GHz [11]. Studies on the EMI shielding performances of polypyrrole/nylon-lycra [12], polythiophene/PET [13], polyaniline/carbon fiber [14] polyaniline/cotton [15,16], and polyethylenedioxythiophene/PET [17] were also examined under different frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks at 1156 cm -1 and 810cm -1 corresponding to C-H plane stretching vibration of quinoid rings and C-H out plane bending vibration of benzenoid rings. The formation of Al-ZnO-POTnanocomposites showed an absorption peaks are centered at around 3459, 1634, 1371and 527 cm -1 respectively [23]. Comparing to that of pure POT polymer, the absorption peaks of Al-ZnO-POT nanocomposites have been shifted to lower wave numbers, the shift of absorption peaks may be corresponding to the formation of hydrogen bonding between Al-ZnO and the -NH group of POT polymer on the surface of the Al-ZnO nanoparticles.…”
Section: Ftir -(Fourier Transform Infra-red Spectroscopy) -Analysismentioning
confidence: 99%
“…The SE A and SE R can be described in terms of R, T, |S 11 |, and |S 21 | as 58,64 i k j j j y { z z z i k j j j j j y…”
Section: Acs Applied Nano Materialsmentioning
confidence: 99%